2013
DOI: 10.11622/smedj.2013145
|View full text |Cite
|
Sign up to set email alerts
|

Carbimazole-induced myositis in the treatment of Graves’ disease: a complication in genetically susceptible individuals?

Abstract: A 24-year-old Chinese woman with Graves' disease presented with myositis two months after treatment with carbimazole. The patient's myositis resolved with hydration and cessation of carbimazole. No other causes of myositis were found, and a change in the medication to propylthiouracil was uneventful. Review of the literature suggests a possible genetic susceptibility, as the majority of reported cases are Asian in origin, similiar to patients who present with thyrotoxic periodic paralysis. Changing the antithy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…In literature, ATDs-related myopathy is rare and mostly involves methimazole (MMZ) and CMZ ( 3 - 9 ), but PTU-related myositis has also been reported ( 10 ). A recent review of these 14 reported cases suggested a possible genetic susceptibility in Asian and female preponderance ( 5 ). Our patient falls in this category.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In literature, ATDs-related myopathy is rare and mostly involves methimazole (MMZ) and CMZ ( 3 - 9 ), but PTU-related myositis has also been reported ( 10 ). A recent review of these 14 reported cases suggested a possible genetic susceptibility in Asian and female preponderance ( 5 ). Our patient falls in this category.…”
Section: Discussionmentioning
confidence: 99%
“…Management of myopathy varied among reported cases. Dose reduction of MMZ or CMZ ( 4 , 6 , 9 ), cessation of MMZ or CMZ and switching to PTU ( 3 , 5 , 9 ), or addition of levothyroxine ( 4 , 6 - 8 ) had led to resolution of myopathy. The exact pathophysiology of the myopathy is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has found that oral ATDs related myopathy was mostly involved MMI and carbimazole, [ 15 , 16 ] PTU has also been reported. Carbimazole is rarely used in China.…”
Section: Discussionmentioning
confidence: 99%
“…So this side effect may tend to genetic susceptibility. [ 16 ] We should pay more attention to this adverse effect on Chinese GD patients.…”
Section: Discussionmentioning
confidence: 99%